Gonad maturity of simping Placuna placenta, Linn 1758 (Bivalve: Placunidae) harvested from Kronjo Coastal, Indonesia - Yon Yonvitner; Isdradjad Setyobudiandi; Rokhmin Dahuri; Jamilah Jamilah (Syiah Kuala University, 2020)
Simping (P. placenta) is a coastal resource found in shallow water with a muddy substrate. Simping widely used as a source of food and as raw material for the decoration. Utilization of simping until now has not yet focused on recruitment, reproductive aspect. This information is important as a basis data for determining the size of the simping catch. This study aimed to find out about of reproduction aspect, determining sex ratio the size of the catch simping. This research was conduct for three months at 3 locations. The number of samples in the analysis is 36 species to determine sex ratio and gonad maturity. Sex ratio indifferent from male and female, but based on the time sex ratio of simping significant, both male and female. The length size of gonads shellfish matures form 5.50 cm and 5.85 cm at 2 TKG conditions. Length of simping mature from 6.08 cm, 6.24 cm, 6.45 cm and 7.11 cm dominant at TKG mature stage 3, and 8.61 cm dominant at 4 TKG conditions. Sex ratio reaches 6 cm shell length and not significant between males and females (M: F=1;1). It is concluded that the level of maturity of gonads increases with increasing of simping size.